A computerized adaptive test for measuring the physics critical thinking skills in high school students - Aang Zainul Abidin; Edi Istiyono; Nunung Fadilah; Wipsar Sunu Brams Dwandaru (Institute of Advanced Engineering and Science, 2019)
Classical assessments that are not comprehensive and do not distinguish students' initial abilities make measurement results far from the actual abilities. This study was conducted to produce a computerized adaptive test for physics critical thinking skills (CAT-PhysCriTS) that met the feasibility criteria. The test was presented for the physics subject of 11th grade high school students with two-tier multiple-choice format. This development research was based on the 4-D model combined with the test development model by Oriondo & Antonio. Eleven experts and 577 11th grade high school students in Kulonprogo, Indonesia, have participated. The media feasibility and the content validity of the items was assessed by experts, while item and abilities parameters were estimated by item response theory. The results obtained: 1) CAT media was declared very feasible and content validity of 136 items was declared valid; 2) all items fitted to partial credit model, the item reliability was classified as good, and the difficulty index of items was good; 3) the results of the CAT-PhysCriTS were equivalent to students academic achievement. Based on the results, CAT-PhysCriTS has fulfilled the requirements as a measuring instrument with measurement times were faster and more comprehensive for large-scale assessments.